Corrosion Resistance of Directionally Solidified Casting Zinc-Aluminum Matrix - Ares, Alicia Esther (2012)
Composite materials obtained by solidification of alloys have made remarkable progress in its development and applications in automotive and aerospace industries in recent decades. Among them the most current application are the zinc and aluminum base (Long et al., 1991; Rohatgi, 1991). Also, it was established that the corrosion behavior of MMCs is based on several factors such as: the composition of the alloy used, the type of reinforcement particles used, their size and distribution in the matrix, the technique used for the manufacture, and the nature of the interface between the matrix and reinforcement. A very slight change in any of these factors can seriously affect the corrosion behavior of the material. In short, there is little research related to the study of mechanical and electrochemical properties of Zn-Al alloys and SiC and Al2O3 composites with different grain structures in the matrix. Also, on the performance of composite materials in corrosive environments and no reported research related to the performance of MMCs in corrosive environments, depending on the solidification microstructure and type of particle distribution.  In the present research, Zn-Al-SiC and Zn-Al-Al2O3 composites were prepared and solidified by vertical directional solidification method. By means of voltammograms and electrochemical impedance spectroscopy data, the corrosion resistances of Zn-Al matrix composite materials with different types of particles are analyzed and the results are compared.